Acute Severe Heart Failure Reduces Heart Rate Variability: An Experimental Study in a Porcine Model - Naar, Jan; Mlcek, Mikulas; Kruger, Andreas; Vondrakova, Dagmar; Janotka, Marek; Popkova, Michaela; Kittnar, Otomar; Neuzil, Petr; Ostadal, Petr (International journal of molecular sciences, 2022)
There are substantial differences in autonomic nervous system activation among heart (cardiac) failure (CF) patients. The effect of acute CF on autonomic function has not been well explored. The aim of our study was to assess the effect of experimental acute CF on heart rate variability (HRV). Twenty-four female pigs with a mean body weight of 45 kg were used. Acute severe CF was induced by global myocardial hypoxia. In each subject, two 5-min electrocardiogram segments were analyzed and compared: before the induction of myocardial hypoxia and >60 min after the development of severe CF. HRV was assessed by time-domain, frequency-domain and nonlinear analytic methods. The induction of acute CF led to a significant decrease in cardiac output, left ventricular ejection fraction and an increase in heart rate. The development of acute CF was associated with a significant reduction in the standard deviation of intervals between normal beats (50.8 [20.5−88.1] ms versus 5.9 [2.4−11.7] ms, p < 0.001). Uniform HRV reduction was also observed in other time-domain and major nonlinear analytic methods. Similarly, frequency-domain HRV parameters were significantly changed. Acute severe CF induced by global myocardial hypoxia is associated with a significant reduction in HRV.
Keywords: prasata; Swine; Stroke Volume; Ventricular Function, Left; funkce levé komory srdeční; srdeční selhání; Heart Rate; Hypoxia; srdeční frekvence; tepový objem; Myocardial Ischemia; acute heart failure; heart rate variability; Animals; ženské pohlaví; Heart Failure; zvířata; pig; ischemická choroba srdeční; Female; experimental model; hypoxie